1988
DOI: 10.1183/09031936.93.01100902
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal asthma: snoring, small pharynx and nasal CPAP

Abstract: We studied two populations of patients who snored and had frequent nocturnal asthma attacks: ten overweight men presenting with typical obstructive sleep apnoea syndrome, and a group of five adolescents with regular snoring and an increase in negative inspiratory oesophageal pressure during stage II non-rapid eye movement (NREM) and rapid eye movement (REM) sleep. All subjects presented cranio-mandibular abnormalities at cephalometric evaluation, with a narrow space behind the base of the tongue. Both populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Upper airway closure and snoring could trigger vagally mediated bronchoconstriction 30,66 and worsen AHR, for example, by altering chemical arousal threshold or to resistive loading. 30 An additional postulated trigger for reflex bronchoconstriction is stimulation of the carotid body by the accompanying hypoxia. 67…”
Section: Neural Reflex Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Upper airway closure and snoring could trigger vagally mediated bronchoconstriction 30,66 and worsen AHR, for example, by altering chemical arousal threshold or to resistive loading. 30 An additional postulated trigger for reflex bronchoconstriction is stimulation of the carotid body by the accompanying hypoxia. 67…”
Section: Neural Reflex Theorymentioning
confidence: 99%
“…The cessation of CPAP returned flow rates to levels before therapy. Guilleminault et al 30 studied 10 men with OSA and predominantly nocturnal asthma; more than 6 months of CPAP therapy abolished nocturnal asthma attacks. Five subjects with both daytime and nighttime asthma symptoms had regular snoring and more negative inspiratory esophageal pressures during sleep (indicative of increased upper airway resistance).…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Nocturnal airway narrowing results in poor sleep quality (6]. It has recently been reported that both snoring and sleep apnoea may precipitate nocturnal airway narrowing in asthmatics (7,8], but the prevalence of snoring and sleep apnoea in asthmatics is unknown. We have, therefore, also examined the fre-Methods A 15 page questionnaire, consisting of 92 questions, was sent by mail to 500 subjects at each of the following eight locations: Lerwick, Thurso, Aberdeen, Ayr, Leeds, Coventry, Southampton and St Helier.…”
mentioning
confidence: 99%